Abbasid Power Under Abu Ja’far Al-Mansur Through Ibn Khaldun’s Ashabiyah Concept - H, Sopyan; M. Sewang, Ahmad; Hasaruddin, Hasaruddin; Zanilha, Muflihah (Rihlah : Jurnal Sejarah dan Kebudayaan, 2025)
The Abbasid dynasty, one of the most successful in Islamic history, emerged from a revolution that overthrew the Umayyad Caliphate. This study examines the role of Abu Ja'far al-Mansur, the second Abbasid caliph, in establishing power and upholding the dynasty's stability and legitimacy. Using a qualitative methodology rooted in historical research, a comprehensive literature review analyzes the historical context of the Abbasid revolution, al-Mansur's contributions, and Ibn Khaldun's concept of ashabiyah. The findings demonstrate that al-Mansur's diverse strategies, including urban development, economic reform, military organization, and ideological governance, were crucial in strengthening Abbasid power. The establishment of Baghdad as the capital, the integration of various ethnic groups, and the promotion of religious legitimacy through alliances with the ulama were key factors in enhancing the dynasty's resilience. The Umayyad dynasty served as a common enemy, fostering solidarity (asabiyyah) among various factions and facilitating the rise of the Abbasids. Al-Mansur's inclusive policies strengthened loyalty and resolved divisions within the empire. This study concludes that al-Mansur was a transformative leader who successfully unified the political, religious, and social spheres, embodying the principles of asabiyyah and establishing a pattern of ideological solidarity that sustained Abbasid rule for centuries. The implications of these findings highlight the importance of an interdisciplinary approach, the relevance of the concept of asabiyyah in the modern context, the significance of the common enemy narrative, and the need for further social theory studies on al-Mansur's leadership.   Dinasti Abbasiyah, salah satu dinasti yang paling sukses dalam sejarah Islam, muncul dari sebuah revolusi yang menggulingkan Kekhalifahan Umayyah. Studi ini meneliti peran Abu Ja'far al-Mansur, khalifah kedua Abbasiyah, dalam memantapkan kekuasaan dan menegakkan stabilitas serta legitimasi dinasti tersebut. Menggunakan metodologi kualitatif yang berakar pada penelitian sejarah, dengan tinjauan pustaka komprehensif menganalisis konteks sejarah revolusi Abbasiyah, kontribusi al-Mansur, dan konsep ashabiyah dari Ibn Khaldun. Temuan menunjukkan bahwa strategi al-Mansur yang beragam, termasuk pengembangan kota, reformasi ekonomi, organisasi militer, dan pemerintahan ideologis, sangat penting dalam memperkuat kekuasaan Abbasiyah. Pendirian Baghdad sebagai ibu kota, integrasi berbagai kelompok etnis, serta promosi legitimasi keagamaan melalui aliansi dengan para ulama menjadi faktor kunci dalam meningkatkan ketahanan dinasti tersebut. Dinasti Umayyah berperan sebagai musuh bersama, mendorong solidaritas (ashabiyah) di antara berbagai faksi dan memfasilitasi kebangkitan Abbasiyah. Kebijakan inklusif al-Mansur memperkuat loyalitas dan mengatasi perpecahan di dalam kekaisaran. Studi ini menyimpulkan bahwa al-Mansur adalah pemimpin transformatif yang berhasil mempersatukan ranah politik, agama, dan sosial, mewujudkan prinsip-prinsip ashabiyah dan membangun pola solidaritas ideologis yang menopang kekuasaan Abbasiyah selama berabad-abad. Implikasi dari temuan ini menyoroti pentingnya pendekatan interdisipliner, relevansi konsep ashabiyah dalam konteks modern, signifikansi narasi musuh bersama, serta perlunya studi-teori sosial lebih lanjut tentang kepemimpinan al-Mansur.